Analysis of wire erosion and workpiece surface roughness in wire electrical discharge machining - Tosun, N; Cogun, C (Professional Engineering Publishing Ltd, 2003)
In this study, the effects of machining parameters on the wire wear, on the size of erosion craters on the wire and on the workpiece surface roughness were investigated experimentally in wire electrical discharge machining (WEDM). An attempt was made to correlate the crater volume and the pulse energy. The experiments were conducted under different settings of pulse duration, open-circuit voltage, wire speed and dielectric flushing pressure. The variations of the wire wear, the size of erosion craters on the wire and the workpiece surface roughness with machining parameters were modelled mathematically by using regression analysis. The relationship between the workpiece surface roughness and the crater size was established. The analysis of variance (ANOVA) and F-test were performed to obtain statistically significant process parameters and the percentage contribution of these parameters to the performance outputs.
Keywords: WEDM; wire wear; crater sizes; surface roughness